Competência informacional na gestão de instituições de ensino superior privadas - Joubert Roberto Ferreira Fidelis (2013)
Information literacy, a construct that correlates the skills, attitudes and knowledge necessary to give the appropriate treatment of information to support decision making and the development of growth strategies of organizations, with numerous studies in education area is still poorly developed in workplace. Thus, the main objective of this research was to understand what is Information Literacy in the workplace, having as object of study the private nonprofit higher education institutions. The interpretation of the phenomena and the allocation of meanings were fundamental in this process of research, because it is an attempt to determine the constitution of an underlying attribute to an individual and with extremely subjective character: the Information Literacy. From mainly the concept of Informational Orientation, developed by Marchand, Kettinger and Rollins (2004), and Information Literacy standards proposed by the Association of College and Research Libraries (2000), this research allowed to develop a construct of Information Literacy facing workplace environments leading into account the rich published literature on the concept in educational area. To check its validity was elaborated and applied a questionnaire to academic managers of a nonprofit educational group, plus an interview for further qualitative study of the concept proposed here. The questionnaire also allowed walking in order to create a tool, which permits to link the skills of professionals dealing with information, develop appropriate informational attitudes and values and use IT to support organizational activities, in order to achieve a high standard of performance.